Perilaku Konsumen di Era Digital Tinjauan terhadap Pembaca HAI Online - Nurhablisyah, Nurhablisyah (Magenta | Official Journal STMK Trisakti, 2017)
Hai magazine announced that Hai Juli 2017 edition is the last printed magazine being published. This meant, Hai as one of the oldest teenage magazine in Indonesia has to follow the other printed media, which being vanished. This magazine has gained 35 years published but have to gave up and choose online publishing. Before Hai magazine, onather printed media such as Sinar Harapan, Tempo, Femina, etc has to stop printing. In order to survice in mass media field, Hai must understand marketing strategy in digital era by understanding consumer behavior in digital era. This research is using qualitative methods and collecting data by literature and observation technique to www.hai.grid.id. The research was done in Jakarta in June to Juli 2017. The result showed, hai online readers are teenage boy, has an online acitivity in dayli life, having smartphone or other device connected to internet, have special budget to stay connected online, love to hang out with friends and community or peer group. This youngsters are also concern about their looks and having interest on music, sports, movie, art or aoutomotive. Life style is basic principle of the magazine. By using simple visual style on their sites, Hai online, more focus on information content. On the online site, Hai provide comments column and invites the readers to send their creation such as videos, photos, graphics, etc. This effort is to stay connect with readers and gained more readers around Indonesia.